ANALYSIS OF THE INDEPENDENT CURRICULUM OF LEARNING AQIDAH AKHLAK MATERIAL AT SMK YPPI SURABAYA - Fitria, Nurul; Masnawati, Eli (Molang: Journal Islamic Education, 2024)
This study aims to analyze the implementation of the Independent Learning Curriculum in the subject of Aqidah Akhlak at SMK YPPI Surabaya. The Independent Learning Curriculum is a new initiative from the Indonesia government that emphasizes learning flexibility and holistic student competency development. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of the Independent Learning Curriculum at SMK YPPI Surabaya has had a positive impact on improving students' understanding of Aqidah Akhlak material. Teachers have an important role in designing interactive and contextual learning according to the needs of students. In addition, the challenges faced include limited resources and adaptation to curriculum changes. However, with collaborative efforts between teachers, students, and school management, the implementation of the Independent Learning Curriculum is able to improve the quality of Aqidah Akhlak education and form the character of students with noble character.